1996
DOI: 10.1084/jem.184.4.1435
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma regulates platelet endothelial cell adhesion molecule 1 expression and neutrophil infiltration into herpes simplex virus-infected mouse corneas.

Abstract: SummaryIn a mouse model of herpes simplex virus (HSV) 1 corneal infection, tissue destruction results from a CD4 + T cell-mediated chronic inflammation, in which interleukin 2 and interferon (IFN)~/are requisite inflanunatory mediators and polymorphonuclear leukocytes (PMN) are the predominant infiltrating cells. In vivo neutralization of IFN-y reheved inflammation at least in part through a specific block of PMN extravasation into HSV-l-infected corneas. Intercellular adhesion molecule (ICAM) 1 and platelet e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 43 publications
5
77
1
2
Order By: Relevance
“…Our findings that PECAM-1 mediates neutrophil extravasation from limbal vessels are consistent with those of Tang and Hendricks (13), who demonstrated that PECAM-1 expression mediates neutrophil recruitment to the cornea in herpes simplex keratitis and that both are regulated by IFN-␥. PECAM-1 is also important in neutrophil infiltration to other tissues, including the lungs and peritoneal cavity (20 -23).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that PECAM-1 mediates neutrophil extravasation from limbal vessels are consistent with those of Tang and Hendricks (13), who demonstrated that PECAM-1 expression mediates neutrophil recruitment to the cornea in herpes simplex keratitis and that both are regulated by IFN-␥. PECAM-1 is also important in neutrophil infiltration to other tissues, including the lungs and peritoneal cavity (20 -23).…”
Section: Discussionsupporting
confidence: 92%
“…Tlymphocytes are mediating this form of corneal inflammation, and CD4 + T-cell derived cytokines such as interferon (IFN)-γ and interleukin (IL)-2 are critical for the development of the disease (Hendricks et al, 1992;Niemialtowski and Rouse, 1992;Tang et al, 1997;Tang and Hendricks, 1996). Polymor-phonuclear neutrophils (PMN) are the most prominent infiltrating cell type seen in HSK (Meyers-Elliott and Chitjian, 1981) and are associated with elimination of HSV-1 from the infected eye Tumpey et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although PMNs are one of the initial cells that traffic to the cornea [3], CD4 + and CD8 + T lymphocytes are thought to be key components in the development of lesions associated with herpetic stromal keratitis [4][5][6][7]. Th2 cytokines exacerbate HSV-1 infection whereas Th1 cytokines are principally produced by those cells infiltrating the infected tissue and contribute towards resistance to virus replication and spread [8][9][10].…”
Section: Introductionmentioning
confidence: 99%